Understanding policy responses to COVID-19: the stars haven't fallen from the sky for scholars of public policy. Issue 8 (3rd August 2021) - McConnell, Allan; Stark, Alastair
ABSTRACT: Responses to COVID-19 across the globe are immensely varied and often perplexing. Policy levers, from mask wearing and social distancing to lockdowns and school closures, have been adopted and avoided with equal conviction by decisions makers who believe their measures are appropriate. In some contexts, the global pandemic has been treated with due seriousness by governments and political leaders while in others it has been downplayed to such an extent that it has been framed as a hoax. Every response to the pandemic has produced seemingly zero-sum debates and disputes over the veracity of knowledge bases, while uncertainty reigns as one of the few constants in decision making arenas. While it may be tempting to gravitate to the view that this unimaginable crisis is beyond the capacity of policy scholars to understand, this introductory article sets the scene for dispelling such a notion. It highlights how a number of core policy issues and perspectives, including the politics of problem framing, the limits of an evidence-based approach, and the nature of the public sector, can help bring analytical insights to this unprecedented crisis.